Between Identity, Cultural Revival, and Social Inclusion: Language ‎Revitalization and the Politics of Belonging in Multiethnic Tidore ‎Kepulauan - Arlinah; Andi Sumar Karman; Ramis Rauf (JPI: Jurnal Pustaka Indonesia, 2026)
The article examines how language revitalization operates as both a cultural project and a political strategy in the multiethnic city of Tidore Kepulauan, North Maluku. Focusing on the institutionalization of the Tidore language through local education policy, public campaigns, and cultural initiatives, the study explores how language becomes a symbolic medium for reclaiming historical dignity, negotiating collective identity, and redefining belonging. Drawing on ethnographic fieldwork conducted between June and October 2024, including classroom observations, policy document analysis, and 30 semi-structured interviews with teachers, school principals, education officials, parents, cultural activists, and community leaders, this study reveals the ambivalent effects of language revitalization in a plural society. On the one hand, the policy strengthens Tidore’s cultural pride and challenges the perceived symbolic dominance of Ternate. On the other hand, it generates concerns among non-Tidore communities regarding cultural exclusion, linguistic assimilation, and educational equity. The findings show that language revitalization is not merely a neutral act of preservation, but a contested process shaped by historical memory, symbolic power, and everyday negotiations of identity. The article argues that local language policy in postcolonial and multilingual societies must move beyond ethnic restoration toward inclusive and dialogic models of cultural belonging.